Responding to some of the variables Alkemioahioi serum During in basket ball - Qhadir, Shareef (Journal of Physical Education, 2011)
The objective of this research is to investigate the impact of carrying a basketball game in some variables Alkemioahioip of serum to the basketball players, where the researcher to measure the rate of accumulation of lactic acid and mineral Trkizalamlah rate during the match official and a private key players who have completed the game to end legal. And Tzment search by selecting a sample of six key players and the researcher snapped the blood of players to nine times. Has been determined by temporal area of the search period of time (up to). The research includes pre and post test. The researcher used a statistical process through the program (spss) and it (the arithmetic mean, standard deviation, t.test). And after analyzing the tests before and after it was concluded that the statistically Download the basketball game affect the accumulation of lactic acid and are clustered as well as the loss ratio of mineral salts. The researcher recommended the need to take advantage of these indicators in the training modules as well as after the end of the game